2015
DOI: 10.1093/infdis/jiv419
|View full text |Cite
|
Sign up to set email alerts
|

Human Neutrophils Are Primed by Chemoattractant Gradients for Blocking the Growth ofAspergillus fumigatus

Abstract: The contribution of human neutrophils to the protection against fungal infections by Aspergillus fumigatus is essential but not fully understood. Whereas healthy people can inhale spores of A. fumigatus without developing disease, neutropenic patients and those receiving immunosuppressive drugs have a higher incidence of invasive fungal infections. To study the role of neutrophils in protection against A. fumigatus infections, we developed an in vitro assay in which the interactions between human neutrophils a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(45 citation statements)
references
References 36 publications
0
45
0
Order By: Relevance
“…fumigatus growth [27]. Introduction of an fMLP gradient in the current study prior to delivery of neutrophils resulted in increased recruitment of neutrophils to sites of interaction (S1B Fig), an increase in hyphal exposure to NETs (Fig 4A), and increased fungal branching (Fig 4B).…”
Section: Resultsmentioning
confidence: 70%
See 3 more Smart Citations
“…fumigatus growth [27]. Introduction of an fMLP gradient in the current study prior to delivery of neutrophils resulted in increased recruitment of neutrophils to sites of interaction (S1B Fig), an increase in hyphal exposure to NETs (Fig 4A), and increased fungal branching (Fig 4B).…”
Section: Resultsmentioning
confidence: 70%
“…Although a direct effect of immunosuppressant therapy on neutrophil activity remains controversial, our previous studies indicate that neutrophils from these patients exhibit reduced activity against A . fumigatus [27]. Prophylactic treatment of immunosuppressed patients with broad-spectrum antibiotics, aimed at reducing risk of bacterial infection, is standard practice [52].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the killing of conidia is achieved by nonoxidative lactoferrin-mediated iron sequestration. An additional study has recently examined interactions between human neutrophils and A. fumigatus conidia and hyphae in the presence of various chemoattractants and neutrophil activators [13] . Using a nanoliter culture well system, this study demonstrated that less than a third of conidia form hyphae when incubated with pure neutrophils, an amount that continues to decrease when the cocultures contain a uniform amount of leukotriene B4, but not fMLP.…”
Section: Introductionmentioning
confidence: 99%